Perilaku Prososial Siswa SMP di Era Revolusi Industri 4.0 (Kolaborasi Guru Dan Konselor) - Septiana, Nila Zaimatus (Universitas Nusantara PGRI Kediri, 2019)
Industry Revolution 4.0 (IR-4) is a disrupted era characterized by a change in the old system with a new technology-based system in the form of IoT (Internet of Things). In the world of education the existence of a new system has an impact on changes in mindset, attitudes and behavior of students. Students who have a high dependence on technology tend to be indifferent to the environment. This results in a weak pattern of direct interaction between students and students' prosocial behavior. Prosocial behavior is an action that can provide benefits for both yourself and others in the social environment. This study aims to describe how prosocial behavior of students in the industrial revolution era 4.0 and collaborative efforts of teachers and counselors in improving students' prosocial behavior in schools. The method used in this study is descriptive qualitative. The subjects of this study were teachers and counselors who were selected according to predetermined criteria. Then the data analysis technique uses narrative techniques. The results showed that the prosocial behavior of students in the industrial revolution era 4.0 was decreasing, so that direction and guidance were needed from both teachers and counselors to restore the nature of individuals as social beings. To improve the prosocial behavior of students both teachers and counselors design various collaborative activities that are beneficial to the social life of students at school.